2020
DOI: 10.2478/mspe-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Rare Earth Elements Content in Hard Coal Type 31.1

Abstract: The aim of the article is to present the results of laboratory analyses determining the content of rare earth elements (REE) in hard coal type 31.1. Coal was extracted directly from the mining excavation located in the Upper Silesian Coal Basin. Mass spectrometry tests with ionization in inductively coupled plasma (ICP-MS), were aimed at the quantitative analysis of the share of REE in coal, taking into account the economic aspects of recovery of these elements. Fine ground hard coal samples and ashes obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Slightly higher Sc concentrations (18-21 ppm) were found in rock samples from the bands, roofs and floors of coal seams within the NW part of the USCB (Kokowska-Pawłowska, 2018). Sc concentration reported for Polish hard coal ranges from 0.86 to 20 for the USCB and from 1.5 to 20.5 ppm for the LCB (Baron, 2020). There is no general agreement in the literature regarding the mode of Sc occurrence.…”
Section: Distribution and Stratigraphical Variability Of The Selected...mentioning
confidence: 94%
“…Slightly higher Sc concentrations (18-21 ppm) were found in rock samples from the bands, roofs and floors of coal seams within the NW part of the USCB (Kokowska-Pawłowska, 2018). Sc concentration reported for Polish hard coal ranges from 0.86 to 20 for the USCB and from 1.5 to 20.5 ppm for the LCB (Baron, 2020). There is no general agreement in the literature regarding the mode of Sc occurrence.…”
Section: Distribution and Stratigraphical Variability Of The Selected...mentioning
confidence: 94%
“…Determination of leachability of elements: total Cr, Zn, Cd, Sn, Pb from mortars was carried out by the inductively coupled plasma mass spectrometry (ICP-MS) method with the use of Agilent 7900 ICP-MS. This method is characterized by a low limit of quantification and high selectivity, which enables the simultaneous determination of many elements in complex matrices, such as trace amounts of rare earth elements (REE) in waste [49].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Kolker et al have reported US coal combustion fly ash contains 192–1667 ppm (Kolker et al 2017 ). Baron has reported the average worldwide REM content in hard coal could be 60 ppm (Scott and Kolker 2019 ; Baron 2020 ). Kumari et al have reported 1035 g.ton −1 of REM content in Indian-origin coal bottom ash (Kumari et al 2019 ).…”
Section: Review Of Rem Valorization Technologies From Anthropogenic W...mentioning
confidence: 99%